A New Role for SAG12 Cysteine Protease in Roots of Arabidopsis thaliana - James, Maxence; Masclaux-Daubresse, Céline; Marmagne, Anne; Azzopardi, Marianne; Laîné, Philippe; Goux, Didier; Etienne, Philippe; Trouverie, Jacques (Frontiers in Plant Science, 2019)
Recently it was shown that the SAG12 cysteine protease might be important for nitrogen (N) allocation to the seeds in Arabidopsis thaliana. Compared to the wild type Col cultivated under low nitrogen (LN) conditions, a decrease in yield and N content in the seeds was observed in the SAG12 knockout Arabidopsis mutant (sag12). As no associated leaf senescence phenotype was observed, a possible involvement of SAG12 in the remobilization of N from organs other than the leaves was proposed. The fact that better root N uptake in sag12 could also supplement N mobilization to the seed was explored. Root architecture, N uptake capacity and 15N partitioning were then analyzed in both genotypes (Col and sag12) cultivated under high nitrogen (HN) and LN conditions. No difference in root architecture and root N uptake capacity was observed between sag12 and Col under HN or LN conditions. However, when compared to Col under LN conditions, the 15N partitioning showed that the accumulation of 15N in the roots of sag12 was detrimental to the 15N allocated to seeds. The sequestration of N in the root of sag12 under LN was associated with an increase in the N protein content of roots and a significant decrease in the cysteine protease activity in the roots. Accordingly, we reveal here that SAG12 is strongly expressed in the root stele at the reproductive stage and especially when plants are cultivated under LN conditions. Taken together, these results suggest a new role for SAG12 as a crucial cysteine protease involved in the root remobilization of N to ensure seed filling and to sustain yield when plants are facing low nitrogen availability.